Perceived Facilitators and Barriers to Participating in a Combination Income-Generating HIV Risk-Reduction Intervention Among Adolescent Girls and Young Women in Nigeria: A Qualitative Study - Nwaozuru, Ucheoma; Tijani, Wakilat; Gbajabiamila, Titi; Obiezu-Umeh, Chisom; Uzoaru, Florida; Ezechi, Oliver; Musa, Adesola Z.; Curley, Jami; BeLue, Rhonda; Iwelunmor, Juliet (Frontiers in Reproductive Health, 2021)
Background: Human immunodeficiency virus risk-reduction interventions that include income-generating activities are garnering attention as effective strategies to engage adolescent girls and young women (AGYW) toward HIV risk reduction. To sustain and promote the uptake of these interventions, researchers must understand factors that may encourage or present barriers to AGYW participation in such interventions. This study explores AGYW perceived barriers and facilitators to participation in a school-based combination income-generating HIV prevention intervention in Nigeria. Methods: A convenience sample of AGYW who participated in a school-based combination income-generating HIV prevention intervention were recruited for the study. Data generated from focus group discussions (FGDs) (eight discussion groups comprising 10–12 participants) were analyzed by inductive thematic analysis. Results: A total of 93 participants with a mean age of 15.04 years (SD = 0.89) participated in the FGDs. The study participants identified several facilitators and barriers to participation in the intervention. Three main themes that emerged as facilitators were: (1) involvement of young female facilitators in the delivery of intervention components, (2) opportunity for social interaction with peers during the intervention period, and (3) support and approval from school authorities. Two main themes were also identified as barriers: (1) sexual conservatism from society and parents and (2) challenges in sustaining a microenterprise. Conclusions: Despite the perceived benefits and interest in participation in the intervention, the study participants outlined some challenges that may hinder participation in the intervention components. Addressing barriers, such as stigma associated with the discussion of sexual health-related topics, coupled with the promotion of facilitating factors, such as leveraging context-appropriate intervention delivery modalities, is important for enhancing the engagement of AGYW in HIV risk-reduction intervention. Our findings can guide future research and design of combination income-generating HIV prevention interventions for in-school AGYW in low-resource settings such as Nigeria.